2021
DOI: 10.1002/edm2.303
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and harms of sodium‐glucose co‐transporter‐2 inhibitors (SGLT2‐I) and renin–angiotensin–aldosterone system inhibitors (RAAS‐I) versus SGLT2‐Is alone in patients with type 2 diabetes: A systematic review and meta‐analysis of randomized controlled trials

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…www.nature.com/scientificreports/ Patients using SGLT2i are mostly on combination with ACEI/ARB, which may have a synergistic effect on the kidney 35 . Several studies had shown that the combination of SGLT2i and ACEI/ARB had a better protective effect on heart and kidney, achieved better control of blood glucose, blood pressure and body weight [36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Patients using SGLT2i are mostly on combination with ACEI/ARB, which may have a synergistic effect on the kidney 35 . Several studies had shown that the combination of SGLT2i and ACEI/ARB had a better protective effect on heart and kidney, achieved better control of blood glucose, blood pressure and body weight [36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the cardiorenal protective effect of SGLT2 inhibitors on T2D complicated with CKD is still based on the combined application of RAAS blockade. Another recent meta‐analysis 24 demonstrated that the combination of SGLT2 inhibitors and RAAS inhibitors in the treatment of patients with T2D may be similar in efficacy and safety, if not superior to SGLT2 inhibitors alone. However, all the qualifying studies in their research were based on trials that evaluated the efficacy of SGLT2 inhibitors compared to placebo in T2D and reported subgroup data for those treated with or without RAAS at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…A standardised predesigned data collection form, utilised in previous similar reviews, 23 , 24 was used for data extraction. For each study, data regarding first author and year of publication, study design and baseline characteristics, intervention and comparator characteristics, and outcomes were extracted.…”
Section: Methodsmentioning
confidence: 99%
“…To compare the effect of intensive versus standard BP control on outcomes in those with or without DM, we conducted interaction analyses using meta-regression techniques as done previously. 24 A narrative synthesis was performed for a few studies that could not be pooled. All analyses were conducted using Stata version MP 17 (Stata Corp, College Station, TX, USA).…”
Section: Methodsmentioning
confidence: 99%